Servant Leadership, Ethical Leadership, and Work Engagement: The Mediating Role of Meaningfulness at Work among Lawyers - Cut Datin Imanal Putri (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: In the legal profession, lawyers often face high workloads, ethical pressures, and demanding client expectations, which can affect their psychological well-being and level of work engagement. Leadership plays a vital role in shaping employees' attitudes and experiences at work. Leadership styles such as servant leadership and ethical leadership are increasingly recognized for their potential to foster a supportive and value-driven work environment. Objective: This study aims to examine the influence of two leadership styles, specifically servant leadership and ethical leadership, on work meaningfulness and work engagement among lawyers. Additionally, it also examines whether work meaningfulness mediates the relationships between these leadership styles and work engagement. Methods: This research employed a quantitative, survey-based explanatory design. Data were collected from 262 lawyers who had worked in the same law firm for at least two years, primarily located in Java and Sumatra, Indonesia. To analyze the data, SEM with LISREL version 8.80 was used to examine both direct and indirect relationships among variables. Results: The findings indicate that servant leadership has a significant positive effect on both work meaningfulness and work engagement. Work meaningfulness strongly influences work engagement and serves as a mediator between servant leadership and work engagement. In contrast, ethical leadership does not meaningfully impact work meaningfulness but does have a direct, positive effect on work engagement. Conclusion: Servant leadership is more effective than ethical leadership in fostering meaningful work and sustained engagement among lawyers.